Da imaterialidade cartesiana a materialidade Lamettriana da mente e sua relação com o corpo - Luchini, Marcelo (Khronos, 2017)
Julien Offray de La Mettrie (1709-1751) French physician and philosopher defended as a fundamental concept of his philosophy the materiality of the soul, as the discussions of the eighteenth century concerning the human knowledge and the limits of sense experience imposed the need for in-depth studies on the physiology of the senses and sensitivity. For the doctor-philosopher, the study of man whose structure and functioning of the nerves and the brain must be analyzed in comparison with the animals in order to try to explain the production of thinking becomes the most fertile hypothesis, because to take the medical practice as a guide, La Mettrie want a fusion between philosophy and medicine. Describing the man analogously to a machine, La Mettrie does not reduce the "organic" in "inorganic" properties and conversely the mechanistic physiology of Descartes sheds light on a fundamental issue, the relationship between body and soul - body and mind – in other words, on the functioning of the brain. The attempt to explain the workings of the mind in purely material terms without the Cartesian soul, or in other words, demonstrate how thought could be the result of a particular organization of matter in the brain, has become the part of the reflection of its philosophy and the closer of modern neuroscience